Дослідження взаємодії деформуючого елемента протяжки із оброблюваною поверхнею деталей із графітовмісних чавунів - Єрьомін, П. М.; Чернявський, О. В.; Студенець, С. Ф.; Eryomin, Р.; Chernyavskiy, А.; Studenets, S. (КНТУ, 2014)
Із застосуванням верстатного та допоміжного обладнання розроблена оригінальна методика дослідження впливу деформуючого протягування на стан обробленої поверхні. Результати дослідження дозволять розробити високоефективні конструкції деформуюче-ріжучих протяжок для обробки отворів в деталях із графітовмісних чавунів. An original technique to study the influence of deforming broaching on the condition of the treated surface. The purpose of the study - the impact on the state of the deforming broaching machined surface of the samples with a graphite cast irons. The possibility to reach the peeling of the surface layer details from cast iron during processing deforming broaching, and the required number of cycles of deformation is much smaller than for the processing of carbon steel. Results of the study will help to develop a highly efficient design deforming - cutting broaches for holes in the details of the graphite cast irons.
Investigation of the interaction of deforming element broach with the treated surface of a graphite cast iron parts
Keywords: деформуюче протягування; верстат; графітовмісний чавун; шорсткість; пластична деформація; deforming broaching; machine; graphite cast iron; roughness; plastic deformation